The Relationship Between Smartphone Addiction and Academic Procrastination Behavior Among Students - Rana Rani; Kusnadi; Bela Janare Putra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The research is titled “The Relationship Between Smartphone Addiction and Academic Procrastination Behavior Among Students.” The aim of this study is to assess whether there is a correlation between the level of smartphone addiction and academic procrastination behavior among students of the Guidance and Islamic Counseling Study Program at UIN Raden Fatah Palembang. This study employs a quantitative approach with a correlational research type. The population of this research consists of all students from the 2022 cohort of the Islamic Guidance and Counseling Study Program, totaling 81 students; thus, the sampling technique used in this study is probability sampling (random sampling), amounting to 55 students. Data collection was conducted using a questionnaire comprising 23 statements, with the decision-making basis being if rCount > rTable, then the statement is considered valid. The data analysis technique utilized the Pearson product-moment correlation test, with the decision rule being if the value of the Pearson product-moment correlation > rTable, then there is a relationship between the two variables. The findings of this research indicate that the Pearson correlation value (0.606) > rTable (0.266), with the interpretation value falling within the interval of 0.61 to 0.80. Based on the hypothesis testing results obtained by the researcher, it was found that there is a relationship between the level of smartphone addiction and academic procrastination behavior among students of the Islamic Guidance and Counseling Study Program at UIN Raden Fatah Palembang. This is evidenced by the Pearson correlation value (r) of 0.606, indicating a